Simulated Vaginal Fluid: Candida resistant strains biofilm characterization and vapor phase of essential oil effect - Fernandes, Liliana Sousa (2023)
Introduction : Vulvovaginal candidiasis is a disease that affects millions of women worldwide. Oral formulations, topical creams or ointments are the conventional dosage forms, with an increase in drug administration through vaginal via. The use of simulated biological fluids (e.g. vaginal fluid) in the evaluation of antifungal therapies may better mimic the real biological environments and therefore provide a better understanding of the behavior of the antifungal. Methods : The main objective of this work was to compare planktonic growth and biofilm formation of Candida species, on common growth medium, Sabouraud Dextrose Broth (SDB) and on vaginal simulation conditions, Simulated Vaginal Fluid (SVF), through the optical density determination, colony-forming units and scanning electron microscopy. In addition, under the same conditions this study also evaluated the ability of vapor phase of oregano and white thyme essential oils (VP-EOs), potential alternative treatment, to inhibit biofilm formation and to destroy mature biofilms of vaginal isolates, through the colony-forming units determination. Results : Candida isolates maintained the same biofilm formation capacity and morphology in both media (SVF and SDB). Furthermore, the results obtained in this work related with VP-EOs effect agree with results acquired, previously, with SDB. This means that the effect of VP-EOs is not affected by the SVF medium, and that this fluid allows the dissolution of the volatile and bioactive compounds. Conclusions : These results can predict the in vivo behaviour, suggesting a potential effective application of VP-EOs as prophylactic or therapeutic treatment for biofilm-related vulvovaginal candidiasis.